Pencil-beam pattern synthesis with a uniformly excited multi-ring planar antenna. - Vicente-Lozano, M.; Ares-Pena, F.; Moreno, E.
In this paper, we describe the synthesis of pencil-beam power patterns for antennas composed of concentric rings of uniformly excited circular patches. The synthesis is performed by simulated annealing, varying the radii of the patch rings so as to optimize performance parameters. Examples illustrate the potential of the method.
Keywords: Antenna radiation patterns; Optimization methods; Circular arrays; Planar arrays